Differential expression of antimicrobial peptides in psoriasis and psoriatic arthritis as a novel contributory mechanism for skin and joint disease heterogeneity. (3rd May 2016) - Bierkarre, H; Harder, J; Cuthbert, R; Emery, P; Leuschner, I; Mrowietz, U; Hedderich, J; McGonagle, D; Gläser, R
Abstract : Objectives : This study tested the hypothesis that a differential innate immune antimicrobial peptide (AMP) profile was evident between the skin and joints in psoriasis and psoriatic arthritis (PsA) and that PsA synovitis may have a distinct AMP pattern compared to other arthropathies. Method : Twenty-two cases had knee biopsies [10 PsA, eight rheumatoid arthritis (RA), and four osteoarthritis (OA)]. Lesional and non-lesional skin biopsies in psoriasis and control tissue were also obtained (n  =  4 each). Immunohistochemistry with semi-quantitative scoring of both synovium and skin was performed using the following panel of AMPs: S100 A8, S100 A9, human neutrophil peptides 1– 3 (HNP1–3), human β-defensins 2 and 3 (hBD-2 and hBD-3), cathelicidin LL-37, psoriasin (S100 A7), and ribonuclease 7 (RNase 7). Results : Similar expression of S100 A8, S100 A9, and HNP1–3 was detectable in PsA and RA synovium but only in the synovium sublining layer (SSL). No expression of psoriasin, RNase 7, hBD-2, and hBD-3 could be detected in the synovial tissue of PsA, RA, or OA. All psoriasis skin samples exhibited broad expression of all investigated AMPs, with strong keratinocyte expression. Conclusions : Given that some AMPs, especially hBD-2, are genetically linked to psoriasis and are only expressed in the skin, these findings show how differential AMP expression in innate immune responses may contribute to disease heterogeneity between PsA and psoriasis and provides a genetic basis for the non-progression of psoriasis subgroups to PsA.